1998
DOI: 10.1359/jbmr.1998.13.4.731
|View full text |Cite
|
Sign up to set email alerts
|

Collagen-Related Markers of Bone Turnover Reflect the Severity of Liver Fibrosis in Patients with Primary Biliary Cirrhosis

Abstract: The influence of a nonskeletal disease with increased connective tissue synthesis or degradation in the collagenrelated markers of bone turnover has been evaluated in 34 women with primary biliary cirrhosis (PBC; age range 41-81 years), a disease with increased hepatic fibrosis, often associated with osteoporosis. Serum osteocalcin (BGP), and carboxy-terminal (PICP) and amino-terminal (PINP) propeptides of type I collagen were assessed as indexes of bone formation, whereas serum tartrate-resistant acid phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
2
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 38 publications
3
40
2
5
Order By: Relevance
“…22 It has been shown that in patients with PBC, NTx levels do not accurately correlate with bone turnover. 39 Collagen-derived markers of bone turnover are influenced by liver collagen metabolism, and appear to be affected in the setting of extensive liver fibrosis. 39 Almost half of the patients in the alendronate group in our study had histologically advanced liver disease (stages 3-4); therefore, the measured markers were probably affected by histological stage and did not adequately reflect changes in bone turnover.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 It has been shown that in patients with PBC, NTx levels do not accurately correlate with bone turnover. 39 Collagen-derived markers of bone turnover are influenced by liver collagen metabolism, and appear to be affected in the setting of extensive liver fibrosis. 39 Almost half of the patients in the alendronate group in our study had histologically advanced liver disease (stages 3-4); therefore, the measured markers were probably affected by histological stage and did not adequately reflect changes in bone turnover.…”
Section: Discussionmentioning
confidence: 99%
“…39 Collagen-derived markers of bone turnover are influenced by liver collagen metabolism, and appear to be affected in the setting of extensive liver fibrosis. 39 Almost half of the patients in the alendronate group in our study had histologically advanced liver disease (stages 3-4); therefore, the measured markers were probably affected by histological stage and did not adequately reflect changes in bone turnover. Furthermore, it is known that NTx levels are lower in postmenopausal women receiving hormone replacement therapy compared with those not receiving hormones, 40 and a large percent of our study patients were on concomitant estrogen therapy.…”
Section: Discussionmentioning
confidence: 99%
“…У реципиентов после ОТП большинство исследователей анализи-руют изменения продуктов деградации коллагена 1-го типа, определяемые в моче или в сыворотке крови [4,9,11,17]. Вместе с тем имеются данные, что при патологических условиях в печени акти-визируются процессы отложения неспецифиче-ских фибриллярных коллагенов 1, 3 и 5-го типов [18,33], и следовательно, деградация некостного коллагена может явиться причиной завышенной оценки деградации костного коллагена 1-го типа, в частности бета-изомера С-терминального тело-пептида коллагена 1-го типа (бета-кросслапсов). В последнее время появились работы о высокой прогностической значимости сывороточной кост-ной фракции 5б тартрат-резистентной кислой фос-фатазы (КТРКФ-5б) -маркера остеокластической активности, который имеет низкую дневную ва-риабельность и не накапливается в циркулирую-щей крови в случае почечной или печеночной па-тологии [23].…”
Section: вестник трансплантологии и искусственных органовunclassified
“…С другой стороны, тепловая и хо-лодовая ишемия могут привести к дегенеративным изменениям клеток донорской печени и развитию миофибробласт-зависимому синтезу коллагена 1-го типа [32]. Хирургическое вмешательство и неполное восстановление функции трансплантата могли явиться причинами выработки фибробласта-ми печени неспецифических коллагенов, и в част-ности, коллагена 1-го типа, как это было отмечено у больных с хроническими заболеваниями пече-ни [18,31]. Более того, гистоморфометрическая оценка процессов резорбции и костеобразования у реципиентов через 4 месяца после ОТП показа-ла, что на фоне выраженного усиления процессов формирования кости (увеличение числа остео-бластов и объема вновь минерализованной кости) число клеток остеокластического ряда и площадь зоны резорбции практически не изменились [20].…”
Section: обсуждение результатовunclassified
“…Guañabens N et al [40] evaluated the bone turnover markers N-telopeptide of type I collagen (NTX), C-telopeptide of type I collagen (CTX) and N-terminal pro-peptide of collagen type I (PINP) in 34 women with primary biliary cirrhosis, a disease with increased liver fibrosis. The aim was to evaluate the influence of a nonskeletal disease with increased connective tissue synthesis or degradation on the levels of the bone turnover markers.…”
Section: The Neo-epitope Approachmentioning
confidence: 99%